SAT0508 Coexistence of Gout and Pyrophosphate Arthritis in Two Large Cohorts: Hyperuricemia as A Factor for Clinical Misdiagnosis. (10th June 2014) - Perez-Ruiz, F.; Castillo, E.; Chinchilla, S.P.; Herrero-Beites, A.M.
Abstract : Background: a definite diagnosis for gout and pyrophosphate arthritis require identification of urate and pyrophosphate crystals in biolόgica samples. That might explain why databases do not capture with acuracy the coexistence of both diseases. Objectives: to evaluate the coexistence of pyrophosphate arthritis in patients with crystal-proved gout and prevalence of hiperuricemia and gout in patients with crystal-proved pyrophosphate arthritis, along with those factors associated. Methods: analysis of data from a cohort of patients with gout and prospective follow-up and a cohort of patients with pyrophosphate arthritis (PPA) in whom data were collected at diagnosis. Diagnosis of gout and pyrophosphate arthritis was base don observation of crystals in sinovial fluid samples (or from tophi) using optic microscopy with polarized light and red compensator, and contrast-phase microscopy if negative. In addition, as per protocol, x-ray or ultrasound prove of chondrocalcinosis was needed for the diagnosis of pyrophosphate arthritis. All samples were evaluated by a EULAR/ACR validated observer. The datasets for cohorts received approval from the Ethical and Clinical Investigation Board. In both datasets general data, data regarding severity of the disease and comorbid conditions are captured. Results: the gout cohort (1992-2013) included 1, 012 patients, 794 (78.5%) of them with a diagnosis confirmed by urate crystal observation; 682 (85.8%) with >1 joint ever involved; the la PPA cohort included 305 patients (2008-2013), 210 (69.9%) with > joint ever involved. The cumulated prevalence of PPA in patients with gout (mean follow-up was 44 months) in patients with a definite diagnosis of gout was 57/794 (7.18%); in 15 of them both pyrophosphate and urate crystals were present in a synovial fluid sample (1.9% in the cohort, 26.3% of patients with coexistence of both diseases). Age (72±11 vs. 59±12) and diuretic prescription (30/57, 52.6% vs. 208/737, 28.2%) were signifficantly associated to coexistence of both diagnosis. The overall prevalence of hiperuricemia in patients with PPA was 70/295 (23.7%), 49/246 (19.9%) in patients with isolated PPA crystals, 6/27 (22.2%) in patients with a previous crystal-proved diagnosis of gout, and in 15/22 (68.2%) of the patients who showed both PP and urate crystals in the same synovial fluid sample. Prescription of diuretics was significantly associated with the presence of hyperuricemia (42/70, 60% vs. 75/225, 33.3%) and to coexistence of both diagnosis (13/22, 59.1% vs. 95/254, 37, 4%; age, renal function and, serum magnesium levels were not statistically different. Conclusions: coexistence of both gout and pyrophosphate arthritis is not an infrequent finding in rheumatology clinical practice when a systematic approach to crystal-proved diagnosis is intended. Aging and diuretic use are factors associated to coexistence of both diagnosis. Hyperuricemia is frequent in elder patients with pyrophosphate arthritis, and may lead to clinical misdiagnosis. Disclosure of Interest: F. Perez-Ruiz Consultant for: Astra-Zeneca, Menarini, Metabolex, Novartis, Pfizer, SOBI, Speakers bureau: Menarini, E. Castillo: None declared, S. Chinchilla: None declared, A. Herrero-Beites: None declared DOI: 10.1136/annrheumdis-2014-eular.5305